Sistem Imbalan Dalam Pendidikan Islam - Rizandi, Hidayat; Jamilus, Jamilus (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
One of the most important components in improving education is employees, or people who work and are paid for their work. However, employee rights are often not fulfilled properly, leading to poor performance. will greatly affect the survival of the institution in the long run. Because the teachings of Islam want their people to work hard, so that they will obtain lawful results from their work, they are very concerned about the existence of workers. The purpose of this study is to see the understanding of the reward system, the purpose of rewarding, types of rewards, the reward system and factors that affect rewards. The research method used is library research. Keywords : System, Rewards, Islamic Education